A coordinating harmonic suppression strategy of a DC microgrid. Issue 16 (17th December 2018) - Xu, Hailiang; Feng, Yunpeng; Xu, Jianwei; Zhang, Yufeng; Wang, Shinan
Abstract : Here, a coordinating harmonic suppression strategy of a DC microgrid was proposed. The harmonics introduced from the connected grid and those generated by local non‐linear loads were both considered and evaluated. Then, a coordinating harmonic suppression strategy was presented for two targets. One is to suppress the voltage pulsating in the DC bus capacitor, which aims to mitigate the adverse impact of the grid voltage harmonics. The other is to obtain sinusoidal output voltage waveforms, that is, to improve the power quality of the microgrid system by properly eliminating the harmonics introduced by the non‐linear loads. Simulation studies indicated that the proposed coordinating control can enhance the system stability and ameliorate the power quality of the load side inverters as well.